HLA and KIR Associations of Cervical Neoplasia. (7th August 2018) - Bao, Xiao; Hanson, Aimee L; Madeleine, Margaret M; Wang, Sophia S; Schwartz, Stephen M; Newell, Felicity; Pettersson-Kymmer, Ulrika; Hemminki, Kari; Tiews, Sven; Steinberg, Winfried; Rader, Janet S; Castro, Felipe; et al.
Abstract : HLA and killer immunoglobulin-like receptor alleles were assessed for association with cervical neoplasia. Our findings suggest HLA-C1 group alleles protect against human papillomavirus type 16–related cervical neoplasia, mainly through a KIR -mediated mechanism. Abstract: Background: Cervical cancer is the fourth most common cancer in women, and we recently reported human leukocyte antigen ( HLA ) alleles showing strong associations with cervical neoplasia risk and protection. HLA ligands are recognized by killer immunoglobulin-like receptors (KIRs) expressed on a range of immune cell subsets, governing their proinflammatory activity. We hypothesized that the inheritance of particular HLA-KIR combinations would increase cervical neoplasia risk. Methods: Here, we used HLA and KIR dosages imputed from single-nucleotide polymorphism genotype data from 2143 cervical neoplasia cases and 13858 healthy controls of European decent. Results: The following 4 novel HLA alleles were identified in association with cervical neoplasia, owing to their linkage disequilibrium with known cervical neoplasia–associated HLA-DRB1 alleles: HLA-DRB3*9901 (odds ratio [OR], 1.24; P = 2.49 × 10 −9 ), HLA-DRB5*0101 (OR, 1.29; P = 2.26 × 10 −8 ), HLA-DRB5*9901 (OR, 0.77; P = 1.90 × 10 −9 ), and HLA-DRB3*0301 (OR, 0.63; P = 4.06 × 10 −5 ). We also found that homozygosity of HLA-C1 group alleles is a protective factor for human papillomavirus type 16 (HPV16)–related cervical neoplasia ( C1/C1; OR, 0.79; P = .005). This protective association was restricted to carriers of either KIR2DL2 (OR, 0.67; P = .00045) or KIR2DS2 (OR, 0.69; P = .0006). Conclusions: Our findings suggest that HLA-C1 group alleles play a role in protecting against HPV16-related cervical neoplasia, mainly through a KIR -mediated mechanism.